Pengaruh Penggunaan Teks Berwarna Dalam Pembelajaran Peluang Terhadap Hasil Belajar Siswa SMA PGRI Cicurug - Agata Fanny Pakpahan; Shabrina Zainuba Azahra; Yesa Rismawati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the effect of using colored text on student learning outcomes in opportunity material and to see students' interest in learning using colored text. This research design uses Pretest-Posttest Control Group Design. Test questions and questionnaires were used as research instruments. Test questions are given with the aim of measuring student learning outcomes before being given treatment and after being given treatment. Meanwhile, questionnaires are used to determine students' responses to learning whether using colored text or only black and white text. The data analysis technique used is the t-test with a significance level of α = 5% or 0.05. With these calculations, the tcount value is 5.593 and the ttable value is 2.008, so tcount > ttable. So it can be concluded that there is an influence of the use of colored text on student learning outcomes in opportunity material. Based on the validity and reliability test on the research instrument, the calculated r value > r table was obtained so that all items in the questionnaire were valid. Meanwhile, in the reliability test, it was found that the data was reliable.